2017
DOI: 10.17712/nsj.2017.4.20170149
|View full text |Cite
|
Sign up to set email alerts
|

Tumors of the lateral and third ventricle: surgical management and outcome analysis in 42 cases

Abstract: Objectives:To discuss the clinical presentation, pathological diagnosis, and surgical outcome for a series of 42 consecutive patients treated for lateral and third ventricular tumors.Methods:This is a retrospective series study conducted between 2001 and 2015 and included 42 patients (mean age: 25 years; range: 2 months-65 years) with lateral and third ventricle tumors surgically treated at King Khaled University Hospital, Riyadh, Kingdom of Saudi Arabia. Demographic, clinical, radiological, surgical, histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The thalamostriate vein is the largest tributary of the internal cerebral vein and is located in the striothalamic sulcus between the caudate nucleus and the thalamus, beneath the stria terminalis in the body of the lateral ventricle [6]. The thalamostriate vein curves medially around the anterior tubercle of the thalamus, where it merges to the internal cerebral vein at the posterior margin of the foramen of Monro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thalamostriate vein is the largest tributary of the internal cerebral vein and is located in the striothalamic sulcus between the caudate nucleus and the thalamus, beneath the stria terminalis in the body of the lateral ventricle [6]. The thalamostriate vein curves medially around the anterior tubercle of the thalamus, where it merges to the internal cerebral vein at the posterior margin of the foramen of Monro.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of hydrocephalus, tumor location in the posterior third ventricle compartment, tumor spreading to the pineal region, cerebral peduncles or cerebral aqueduct, IV ventricle are the subjects related to the choice of surgical approach [3][4][5]. Depending on tumor location, its size and ventricular hydrocephalus, t r a n s c o r t i c a l t r a n s f o r a m i n a l o r t r a n s c o r t i c a l transchoroidal approach or their combination may be used [6][7][8]. The combination of them -extended transforaminal approach (transforaminal approach with anterior choroidal dissection) makes it possible to reduce postoperative complications, with adequate visualization of the pathology and an acceptable angle of "attack" upon the posterior third ventricle tumor.…”
mentioning
confidence: 99%
“…In his literature review of 33 studies involving seventy patients, Zada et al mentioned only 3 patients of anaplastic intraventricular ODG [1]. Similarly, Sherif M. Elwatidy et al in their analysis of 42 cases of the lateral and third ventricle tumors reported only a single case of ventricular anaplastic oligodendroglioma in adults [6]. Few isolated case reports of intra- ventricular oligodendrogliomas exist in the adult population [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, intraventricular ODG arises from the anterior part of lateral ventricles [5]. ODG in the third ventricle is extremely rare and only a few cases of anaplastic ODG in the lateral and third ventricles have been reported in the literature [6][7][8]. ODG infiltrates locally to meninges [9] and rarely has leptomeningeal spread [9,10].…”
Section: Background and Importancementioning
confidence: 99%
“…In the 1st month, seizure activity may be the result of the change in the CSF circulation and the remodeling of vascular structures. Cortical incisions have more frequently lead to epileptic seizures than transcallosal incisions in human medicine ( 25 – 27 ). Levetiracetam was administered after the surgery to reduce the secondary effects of vascular damage and CSF circulation disturbance ( 28 ).…”
Section: Discussionmentioning
confidence: 99%